2013
DOI: 10.1007/s12603-012-0370-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of depressive symptoms with recurrent falls: A cross-sectional elderly population based study and a systematic review

Abstract: The current cross-sectional study shows an association between abnormal 4-item GDS score and recurrent falls. This association of depressive symptoms with recurrent falls was confirmed by the systematic review. Based on these results, we suggest that recurrent falls risk assessment should involve a systematic screening of depressive symptoms using the 4-item GDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
4
28
0
8
Order By: Relevance
“…De los 24 artículos que integran la muestra, seis fueron publicados en 2011 (16,18,21,31,(34)(35) , cuatro en 2012 (24)(25)33,38) , once en 2013 (17,(19)(20)(22)(23)(27)(28)(29)(30)32,39) y tres en 2014 (26,36,37) . En cuanto al país de origen de los estudios, los Estados Unidos (19,21,25,31,33,35,37) y Australia (17)(18)27,38) representan el mayor número de estudios, con siete y cuatro, respectivamente, seguido de Canadá (22,24,29) y Reino Unido, con tres estudios (26,34,36) .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…De los 24 artículos que integran la muestra, seis fueron publicados en 2011 (16,18,21,31,(34)(35) , cuatro en 2012 (24)(25)33,38) , once en 2013 (17,(19)(20)(22)(23)(27)(28)(29)(30)32,39) y tres en 2014 (26,36,37) . En cuanto al país de origen de los estudios, los Estados Unidos (19,21,25,31,33,35,37) y Australia (17)(18)27,38) representan el mayor número de estudios, con siete y cuatro, respectivamente, seguido de Canadá (22,24,29) y Reino Unido, con tres estudios (26,34,36) .…”
Section: Resultsunclassified
“…En cuanto al país de origen de los estudios, los Estados Unidos (19,21,25,31,33,35,37) y Australia (17)(18)27,38) representan el mayor número de estudios, con siete y cuatro, respectivamente, seguido de Canadá (22,24,29) y Reino Unido, con tres estudios (26,34,36) . Otros estudios son originarios de Japón (23,39) , Francia (28,30) , Brasil (16) , China (32) y Suecia (20) . Fueron seleccionados 23 estudios primarios y una RSL.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Additionally, the diagnostic criteria for depression as low mood, loss of interest and pleasure, insomnia, fatigue, discontinued activities, and feelings of worthlessness and despair [4]. Furthermore, elderly people with an abnormal status for four items of GDS had experienced recurrent falls twice during the past 2 years, and these people were found to exhibit depression [9]. Finally, sleep disturbance as the most frequent symptom of depression in elderly people [11].…”
Section: Defining Characteristics Of Depression In Elderly Peoplementioning
confidence: 99%
“…Based on research findings accumulated over many years, elderly people with mild, early-diagnosed, and relapsed depression exhibit a high risk of dementia [5]. Furthermore, systematically reviewed the literature on the association of depression symptoms with recurrent falls among the elderly population and demonstrated that elderly people with an abnormal status for four items of the Geriatric Depression Scale (GDS) had experienced recurrent falls twice during the past 2 years [9]. Overall, the depression symptoms and disorders influence their health and are the major factors causing a high risk of suicide; thus, depression represents a heavy burden on the family and society [3,4,8].…”
Section: Introductionmentioning
confidence: 99%